Primary Sjögren's syndrome beyond Sicca symptoms: A rheumatology clinic experience - Alam, Hamza; Perveen Umer, Tahira; Nazir, Lubna `; Erum, Uzma; Alam, Nabiha; Irfan, Muhammad (Journal of Fatima Jinnah Medical University, 2019)
Background: Primary Sjögren's syndrome (pSS) is an autoimmune inflammatory disorder characterized by both exocrine glandular as well as extraglandular disease. Despite having known for a primarily glandular affection, the extraglandular manifestations are also frequently reported but not well studied. This study aims to evaluate extraglandular clinical features of pSS occurring as initial manifestations. Patients and methods: This retrospective cohort study was conducted from 1stJanuary 2014 to 1stJanuary 2019 at Liaquat National Hospital, Karachi. It comprised of collected data of patients who presented with extraglandular symptoms as initial manifestations and were diagnosed as pSS. Results: Of the 36 patients, 31 (86.1%) were female while 5 (13.9%) were males. Commonest extra glandular manifestations were arthralgia in 10 (27.7%), fatigue in 6 (16.6%), renal tubular acidosis in 6 (16.6%), peripheral neuropathy in 3 (8.3%), lymphoma in 3 (8.3%), optic neuritis in 3 (8.3%), interstitial lung disease in 2 (5.5%), and Raynaud s phenomenon in 1 (2.7%), Transient ischaemic attacks (TIA) and stroke in 1 (2.7%), and posterior reversible encephalopathy syndrome (PRES) in 1 (2.7%) patient. Conclusion: Primary syndrome is a rare auto immune disease which apart from glandular symptoms may initially manifest with extraglandular symptoms. Though these distressing presentations are rare, they can become potentially life threatening if not recognized early. It is important to keep a high index of suspicion for early diagnosis and management to prevent devastating effects of these complications.